(3GdCQHYhf MOjKkGs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG CQHYhf MOjKkG Yf CQHYjf ef GdUMGHI ef MOjK efgG efJbi ef CQHYjf eaQOI HGdJUfja ai CQHYjf fhYkG ef CfhGY GdJCdja s
(3BNQgG (B:s
(3hddabjg CHj YHO Gddg eMeO Hf CHj GdjeGfi fRjd ecI CQHYhf MOjKkG Yf CQHYjf TjNkG bOehG Edi ecg ef CQHYjf eOjfI HTQW GdChdi s
(3CQHYjf MOjKkG Yf CQHYjf UMGHjkG efJbi ef CQHYjf eaQOI ai CQHYjf fhYkG ef CfhGY GdJCdjas
(3GdfSNI HgG MhGTs
(3JNQjL GdLeGd jhSa Hf GdeHQO GdYeQi GdUGdMis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B54s
Keywords: (3GdMOjK h GdeUWdMs